DIPLOMASI PUBLIK INDONESIA DALAM EVENT MOTOGP MANDALIKAT TAHUN 2022-2023 - Ramadhani, Harits Andrian; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study focuses on Indonesia's public diplomacy during the MotoGP event held in Mandalika from 2022 to 2023. MotoGP is one of the largest motorcycle racing championships in the world, making it an excellent platform for a nation to shape its image. Indonesia was selected as the host country for the MotoGP championship, with Mandalika serving as the venue. Indonesia utilized this opportunity to conduct public diplomacy and nation branding in order to achieve its national interests. The research employs a descriptive qualitative methodology, utilizing various data collection techniques, such as literature reviews from books, journals, websites, and relevant documents. The study adopts a constructivist perspective, incorporating theories of public diplomacy, nation branding, and analysis at the nation-state level. The findings of this study indicate that Indonesia's public diplomacy efforts were carried out through three main forms: government-sponsored diplomacy, cultural diplomacy, and mass media diplomacy. Additionally, Indonesia engaged in nation branding to shape its image, aiming to foster international perceptions of Indonesia as a country rich in natural resources and diverse tourist destinations, thereby enhancing the nation's tourism potential. Keywords: Public Diplomacy, MotoGP, Mandalika, Nation Branding.